Tenofovir Disoproxil Fumarate Use during Pregnancy and Infant Bone Health: the Tenofovir in Pregnancy Pilot Study. Issue 11 (November 2018) - Kourtis, Athena P.; Wiener, Jeffrey; Wang, Liming; Fan, Bo; Shepherd, John A.; Chen, Lili; Liu, Wei; Shepard, Colin; Wang, Linhong; Wang, Ailin; Bulterys, Marc
Abstract : The effects of maternal tenofovir use on infant bone mineral content (BMC) and bone mineral density (BMD) were evaluated in a pilot study of HIV/Hepatitis B-coinfected pregnant women in China. BMD and BMC were assessed at age 6 months of life in 14 tenofovir-exposed and 13 unexposed infants. Trends toward lower BMC and BMD were observed in infants exposed to maternal tenofovir but were not statistically significant.